STUDI PERENCANAAN PROTOTIPE SISTEM OTOMASI METERING GARDU INDUK MENGGUNAKAN KONSEP HUMAN MACHINE INTERFACE - Irwan Heryanto Eryk; Slamet Nurhadi (JURNAL ELTEK, 2018)
This research is studying the automation of substation monitoring system especially in metering equipment. It was aimed to plan and implemented the substation design that monitored with SIMATIC WinCC program. The equipments are PLC, PM-710, SIMATIC WinCC, Movicon, relay, MCB, CT and Transformers. It used 3 phase power supply connected to several load of Resistor (R),Inductor (L), and Capacitor (C). PM-710 was used to measure the outgoing load datas that connected and saved to Personal Computer (PC). The experiment were using the varied load. Base on the module, the power substation simulated with WinCC and the reading metering datas such as real power, apparent power and power factor also frequency by MOVICON that displayed in the PC monitor.